Research on Parking Service Optimization Based on Permit Reservation and Allocation - Duo Xu; Huijun Sun (Journal of Advanced Transportation)
Parking facilities in central urban areas have limited supply, high utilization, and turnover rate, leading to the high parking cost. To draw the issues of parking uncertainty, high search time, and underutilization of parking lots, this study shows the application of permits in parking management. It first analyzes the characteristics and costs of “arrival priority” and “reservation priority” modes, and then, it proposes the parking permit reservation and allocation mode based on “service order optimization” and designs an “ant colony-genetic” algorithm to solve the optimal service order. The numerical example shows that the measures of quantity control and matching optimization are effective in parking management. The parking reservation mode of “service order optimization” has advantages in parking lot utilization rate, service demand quantity, and total parking cost.